THE GOVERNMENT-TAXPAYER GAME - CARFI, David; FICI, Caterina (Theoretical and Practical Research in Economic Fields, 2012)
In this paper, we model - quantitatively – a possible realistic interaction between a taxpayer and his Government. We formalize, in a general setting, this strategic interaction. Moreover, we analyze completely a particular realistic sample of the general model. We determine the entire payoff space of the sample game; we find the unique Nash equilibrium of the interaction; we determine the payoff Pareto maximal boundary, the conservative payoff zone and the conservative core of the game (part of Pareto boundary greater than the conservative payoff of the game). Finally, we suggest possible compromise solutions between the two players. From an economic point of view, the sample chosen gives an example of normative settings, for which, there is no reason (convenience), for the taxpayer, to evade the taxes or to declare less than his real income, when his behavior is conservative (defensive, risk-averse). Moreover, the two proposed compromise solutions (which realize the maximum collective gain) could be significantly applied to distinguished taxpayer (big companies and so on).